Epistemic Alienation in African Scholarly Communications: Open Access as a Pharmakon - Mboa Nkoudou, Thomas Hervé (My University, 2020)
This chapter is published in the book "Reassembling Scholarly Communications: Histories, Infrastructures, and Global Politics of Open Access"
Keywords: Pharmakon; Open Access; African Scholarly Communications